Peningkatan Pemahaman Perkalian Bilangan dengan Menggunakan Metode Bermain Siswa Kelas III SD N 3 Kalikotes - Chitra Novellia (Universitas Sebelas Maret, 2022)
This research aims to improve the understanding of multiplication among third-grade students by employing a play-based method. Conducted using the Classroom Action Research approach, the study spans a two-week period, comprising two cycles. Each cycle consists of two two-hour sessions. The research is conducted with 26 students from the first semester of the third-grade class at SD N 3 Kalikotes Klaten for the academic year 2021/2022. Data collection involves written tests conducted at the end of each cycle, accompanied by observations during each session. The data analysis utilizes descriptive analysis, involving the calculation of average scores and the determination of Minimum Completeness Criteria (KKM). The Classroom Action Research, employing a play-based method in teaching multiplication to third-grade students, has shown an improvement in their understanding of the material.